The Effect of Male Migration on Employment Patterns of Women in Nepal - Lokshin, Michael; Glinskaya, Elena (World Bank, 2012)
What is the impact of male migration on the labor market behavior of women in Nepal? The instrumental variable full information maximum likelihood method is applied to data from the 2004 Nepal Household Survey to account for unobserved factors that could simultaneously affect men's decision to migrate and women's decision to participate in the labor market. The results indicate that male migration has a negative impact on the level of the labor market participation by women in the migrant-sending household. There is evidence of substantial heterogeneity (based on both observable and unobservable characteristics) in the impact of male migration. The findings highlight the important gender dimension of the impact of predominantly male migration on the well-being of sending households. Strategies for economic development in Nepal should take into account such gender aspects of the migration dynamics.